(untitled) (International Journal of Contemporary Security Studies, 2022)
The management of the company and its directors are frequently recognized as potential subjects of criminal liability. It raises the question whether that liability is also applicable on subjects who control or manage the company in an indirect or informal way. With the aim to find the answer, in the first part of the paper, the definition of the term director is analyzed from the aspects of the comparative legal tendencies (de jure, de facto and shadow directors) and domestic positive regulation. Also the paper contains the insight in consequences which the scope of the subjects of the civil liability to a company has on the scope of subjects of the criminal liability (regarding two criminal offences form company law). In the central part of the paper, the analysis of the term responsible person in legal entity is given. Namely, directors (i.e. managing and supervisory board members and individual directors) are only one of possible categories of responsible person in legal entity (however, the most frequent) so the term responsible person in legal entity is considerably wider than the term director. It has been concluded that the definition of responsible person in legal entity form the Criminal Code mainly compensates possible shortcomings of the term director from the domestic company law due to the fact that a person “who is de facto entrusted with discharge of particular duties from the scope of activities of the legal person” is also recognized as responsible person in accordance with a law. Finally, a proposal for potential regulatory improvement is given.